Potential genotoxicity of Salvia pratensis L. aqueous extracts and their biogenic silver nanoparticles - Radović Jakovljević, Marina Z.; Tubić Vukajlović, Jovana M.; Srećković, Nikola Z.; Gašić, Uroš; Mišić, Danijela; Mihailović, Vladimir B.; Milošević-Đorđević, Olivera M. (Archives of Biological Sciences, 2026)
Paper description: Medicinal plants are important sources of bioactive compounds. Plant-based silver nanoparticles are explored for biomedical use. Their potential genotoxic effects require careful evaluation to ensure biological safety. This study investigated aqueous extracts from the root and aerial parts of Salvia pratensis and their biogenic silver nanoparticles using human mononuclear cells and cytogenetic assay. The observed differences in genotoxic and antigenotoxic effects between plant extracts and their corresponding silver nanoparticles highlight tissue-specific and concentration-dependent responses. The study provides new evidence relevant to safety assessment of plant-derived products and biogenic nanoparticles, contributing to their informed and responsible biomedical application. Abstract: Biosynthesis of metal nanoparticles using plant extracts is considered an eco-friendly approach with promising biomedical applications; however, data on their safety, particularly genotoxicity, remain limited. This study evaluated the phenolic composition and genotoxic potential of aqueous extracts from the root (SPR) and aerial parts (SPA) of Salvia pratensis L. and their corresponding biogenic silver nanoparticles (SPR-AgNPs and SPA-AgNPs). Spectrophotometric methods were used to quantify total phenolic and flavonoid contents, and LC-MS analysis was employed to characterize the phenolic profiles. The genotoxic potential of the extracts and AgNPs was evaluated in human lymphocytes via the comet assay, with treatments applied at four concentrations ranging from 25 to 100 µg/mL, either independently or in combination with hydrogen peroxide. Both extracts exhibited high phenolic content, with lower flavonoid levels in SPR. LC-MS analysis identified rosmarinic acid as the predominant compound in SPA and salvianolic acid K in SPR. Both extracts and AgNPs increased DNA damage in lymphocytes. In contrast, only the SPA extract lowered H₂O₂-induced DNA damage, demonstrating a pronounced protective effect. These findings indicate potential genotoxic risks associated with S. pratensis extracts and their AgNPs, while also highlighting selective protective properties depending on the plant part used.